Rancang Sistem Presensi Online dengan Metode Gamifikasi dan Online Collaborative Learning - Dodi Solihudin; Iin Iin; Dian Ade Kurnia (Masoem University, 2022)
Online lectures are still being held while Covid-19 pandemic is going to end. Suitable system is needed to ensure the quality of online learning. We must combine the teleconference with the Collaborative Learning System to maintenance the interactions between students and their lecturer. The research is to build a system that can implement the Collaborative Learning System in online lectures. The methods used are gamification and Extreme Programming. The results of the research is the Online Presence application with chat system features, real-time polling system, real-time question-answer, and real-time leaderboard. The application can be accessed athttps://ikmiapp.web.id/presline.